Spatial modelling of the shared impact of sexual health knowledge and modern contraceptive use among women with disabilities in Africa - Obasanjo Afolabi Bolarinwa; Clifford Odimegwu; Aliu Mohammed; Ezra Gayawan (Contraception and Reproductive Medicine)
Abstract Background Women with disabilities remain highly vulnerable to sexual and reproductive health problems, particularly in sub-Saharan Africa (SSA), where their sexual and reproductive rights, such as access to sexual health information and contraception, are often neglected. This study investigated the spatial patterns of the shared impact of sexual health knowledge and modern contraceptive use among women with disabilities in Africa. Methods We used the most recent Demographic and Health Survey (DHS) data involving 16,157 women with disabilities from ten African countries for this study. The data were analysed using both spatial and Bayesian inference to account for the shared component model patterns between sexual health knowledge and modern contraceptive use among women with disabilities while accounting for factors unique to each outcome. Bayesian inference via the Integrated Nested Laplace Approximation (INLA) was used for implementation. Priors for shared effects ​were set as log-normal distributions, while Gaussian priors were assigned to fixed effects. Intrinsic Conditional Autoregressive (ICAR) priors modelled spatial dependencies between districts, introducing spatial autocorrelation based on shared boundaries. Penalised Complexity (PC) priors controlled precision parameters to balance model complexity. Results The study revealed low sexual health knowledge (ranging from 3% in Nigeria to 27% in Uganda) and modern contraceptive use (ranging from 1% in DR Congo and Chad to 27% in Uganda) among women with disabilities across the countries surveyed. The spatial patterns showed diverse intra-country and inter-country disparities of sexual health knowledge and modern contraceptive use among the women, with lower shared impact observed in Mauritania, Nigeria, Uganda, Chad, and DR Congo relative to Kenya, Malawi, Mali, South Africa, and Rwanda. Factors that influence sexual health knowledge and modern contraceptive use among women with disabilities include education, marital status, place of residence, community literacy level, community socio-economic status, and age. Conclusions and recommendations Sexual health knowledge and modern contraceptive use among women with disabilities in Africa remain low, albeit with varied intra-country and inter-country spatial disparities. Therefore, spatial areas with low sexual health knowledge and modern contraceptive use should be given more attention when implementing measures to promote the use of modern contraceptives among women with disabilities. Promoting sexual health knowledge and modern contraceptive use among women with disabilities in Africa could significantly contribute towards the realisation of the 2030 Sustainable Development Goal agenda of “leaving no one behind”.